57.7k views
2 votes
Drag values to complete each equation.

Drag values to complete each equation.-example-1

1 Answer

2 votes

Answer:

1 and
8^(-1)

Explanation:

using the rules of exponents


(a^m)^(n) =
a^(mn)


a^(m) ×
a^(n) =
a^((m+n))


(a^(m) )/(a^(n) ) =
a^((m-n))

given
(8^3)^(4) ×
8^(-9) /
8^(3)

= (
8^(12) ×
8^(-9) ) /
8^(3)

=
(8^(12+(-9)) )/(8^(3) ) =
(8^(3) )/(8^(3) ) = 1

given (
8^(3) ×
8^(4)) /
(8^2)^(4)

=
(8^((3+4)) )/(8^(8) )

=
(8^(7) )/(8^(8) )

=
8^((7-8)) =
8^(-1)


User Muc
by
5.8k points